2010
DOI: 10.1007/s11207-010-9584-6
|View full text |Cite
|
Sign up to set email alerts
|

Study of Coronal Jets During Solar Minimum Based on STEREO/SECCHI Observations

Abstract: During the 2007 -2008 minimum of solar activity, the internally occulted coronagraphs SECCHI-COR1 onboard the STEREO space mission recorded numerous jet-like ejections over a great range of latitudes. We have found more than 10000 white-light jets in the above-mentioned period. Sometimes they can be identified on the disk with bright points observed in ultraviolet images by EUVI. In this study we present a catalog consisting of jets observed by the SECCHI-COR1 instrument and their association with lower corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 37 publications
3
36
0
Order By: Relevance
“…We found that numerous jets from coronal bright points in coronal holes and at their boundaries do carry high-density plasma at very high speeds throughout the solar atmosphere. It is now known that many of these jets reach the interplanetary space (Paraschiv et al 2010 The concentration of jet-like events in coronal holes and at their boundaries as shown in Paper II and their plasma characteristics obtained here make them an important candidate for one of the sources of the slow solar wind. Most recently, though, Neugebauer (2012) "proposed that the interplanetary manifestations of X-ray jets observed in solar polar coronal holes during periods of low solar activity are the peaks of the so-called microstreams observed in the fast polar solar wind".…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…We found that numerous jets from coronal bright points in coronal holes and at their boundaries do carry high-density plasma at very high speeds throughout the solar atmosphere. It is now known that many of these jets reach the interplanetary space (Paraschiv et al 2010 The concentration of jet-like events in coronal holes and at their boundaries as shown in Paper II and their plasma characteristics obtained here make them an important candidate for one of the sources of the slow solar wind. Most recently, though, Neugebauer (2012) "proposed that the interplanetary manifestations of X-ray jets observed in solar polar coronal holes during periods of low solar activity are the peaks of the so-called microstreams observed in the fast polar solar wind".…”
Section: Discussionmentioning
confidence: 56%
“…The electron density of the jets was found to be 0.7−4 × 10 9 cm −3 while for the flaring site 2.4−10.0 × 10 9 cm −3 . These events are also observed in the ultraviolet (Alexander & Fletcher 1999;Ko et al 2005;Madjarska 2011) and white-light (Paraschiv et al 2010). Paraschiv et al (2010) analysed over 10 000 events observed in white-light by STEREO/SECCHI-COR1, and found that little more than 70% of the white-light jets were associated with EUV jets.…”
Section: Introductionmentioning
confidence: 99%
“…of the bright points as observed in Extreme Ultraviolet Imager (EUVI; Wuelser et al 2004) 195 Å images at the time when the jet was observed in COR1. In Paraschiv et al (2010), we suggested that the number of jets with high outflow speeds is large enough to contribute significantly to the solar wind, and we concluded that these results may point to the mechanism responsible for the expansion of the jet, namely a pressure-driven expansion of the plasma. We later expanded the study (Paraschiv et al 2012) in order to discuss the possible contribution of coronal jets to the solar wind flux, by estimating the ejected particle mass flux of a selected subsample of the abovementioned coronal jets.…”
Section: Introductionmentioning
confidence: 82%
“…In our previous work (Paraschiv et al 2010), we identified and studied white-light jets observed by the SECCHI-COR1 white light coronagraph. We identified more than 10 000 whitelight jets spread across the entire solar limb at the minimum of solar activity between 2007 and 2008.…”
Section: Introductionmentioning
confidence: 99%
“…A narrow CME was detected at 04:37 UT in Large Angle Spectroscopic Coronagraph (LASCO) on board SOHO. The CME may be the coronographic counterpart of the jet (Feng et al, 2012;Paraschiv et al, 2010;Nisticò et al, 2009). The observation was made using the extreme ultraviolet (EUV) passbands of the Atmospheric Imaging Assembly (AIA) onboard SDO.…”
Section: Observations and Data Analysismentioning
confidence: 99%